Matter’s concept mobile learning application / Tuan Nurfatien Izzaty Tuan Azlan - Tuan Azlan, Tuan Nurfatien Izzaty (2017)
Matter’s Concept Mobile Learning Application is a learning tools that help primary school students learn matter concept in their science syllabus. This application was developed by referring some research elements that may ease the way students learn. The methodology used for the project is ADDIE model because it is suitable for most of learning environment. During the development, all the asset and scenes of the project is developed using Unity 5. Usability test has been done for this mobile learning application. The questionnaire was given to the test user to get the result for its functionality, user interface and learning content aspect of the application.